Anna Gerber: capstone - Gerber, Anna, artist (Colorado State University. Libraries, 2026)
The artist's statement: My love for Art started with animated media, I loved the hand drawn look and the fluid motions studios were able to achieve. While I mainly work on still illustrations I've always tried to push myself to get better at adding motion to my work. I've done this through splicing my illustration and manipulating individual parts subtly so that my illustration transforms into a breathing piece. When working on an animated piece I prioritize consistency and forms. I take extra time to go through and make sure my lines are right where I want them to be and don't pull attention away from the movements. I embed the idea of attention to detail in my pieces to increase visual interest and expand on subtle story telling.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art